Convalescent human plasma candidate reference materials protect against Crimean-Congo haemorrhagic fever virus (CCHFV) challenge in an A129 mouse model - Kempster, Sarah; Hassall, Mark; Graham, Victoria; Kennedy, Emma; Findlay-Wilson, Stephen; Salguero, Francisco J.; Bagci, Binnur; Elaldi, Nazif; Oz, Murtaza; Tasseten, Tuba; Charlton, Frank W.; Barr, John N.; et al. (Virus research, 2024)
•Convalescent human plasma can protect against CCHFV challenge in a mouse model.•The protection afforded by the convalescent plasma was titratable.•Defining the protective level of anti-CCHFV antibodies supports vaccine development. Crimean-Congo Haemorrhagic Fever Virus (CCHFV) is spread by infected ticks or direct contact with blood, tissues and fluids from infected patients or livestock. Infection with CCHFV causes severe haemorrhagic fever in humans which is fatal in up to 83 % of cases. CCHFV is listed as a priority pathogen by the World Health Organization (WHO) and there are currently no widely-approved vaccines. Defining a serological correlate of protection against CCHFV infection would support the development of vaccines by providing a ‘target threshold’ for pre-clinical and clinical immunogenicity studies to achieve in subjects and potentially obviate the need for in vivo protection studies. We therefore sought to establish titratable protection against CCHFV using pooled human convalescent plasma, in a mouse model. Convalescent plasma collected from seven individuals with a known previous CCHFV virus infection were characterised using binding antibody and neutralisation assays. All plasma recognised nucleoprotein and the Gc glycoprotein, but some had a lower Gn glycoprotein response by ELISA. Pooled plasma and two individual donations from convalescent donors were administered intraperitoneally to A129 mice 24 h prior to intradermal challenge with CCHFV (strain IbAr10200). A partial protective effect was observed with all three convalescent plasmas characterised by longer survival post-challenge and reduced clinical score. These protective responses were titratable. Further characterisation of the serological reactivities within these samples will establish their value as reference materials to support assay harmonisation and accelerate vaccine development for CCHFV.